2007
DOI: 10.1016/j.ica.2006.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Orthomercurated and cycloaurated derivatives of the iminophosphorane Ph3PNPh

Abstract: Ortho-lithiation of Ph 3 P=NPh followed by reaction with HgCl 2 gave good yields of [Hg{C 6 H 4 (PPh 2 =NPh)-2}Cl], 3, which was characterised spectroscopically and by an Xray crystal structure determination. This is an isomer of the product of direct mercuration of Ph 3 P=NPh which occurs on the N-bonded phenyl ring [Vicente et al, Organometallics, 22 (2003) 4248]. Transmetallation of 3 with [AuCl 4 ]gave the corresponding cycloaurated complex [Au{ 2-C,N-C 6 H 4 (PPh 2 =NPh)-2}Cl 2 ], with a five-membered met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…The trans influence can be seen in the lengthening of the AueCl bond trans to the carbon compared with that opposite the N (2.348(2) Å compared with 2.272(2) Å) for 6a. The bonding parameters involving Au are similar to those reported for (2-Cl 2 AuC 6 H 4 )Ph 2 P]NePh, as are the CeN and N]P bond lengths [6].…”
Section: Crystal Structures Of the Gold(iii) Complexes 6a And 6csupporting
confidence: 78%
See 3 more Smart Citations
“…The trans influence can be seen in the lengthening of the AueCl bond trans to the carbon compared with that opposite the N (2.348(2) Å compared with 2.272(2) Å) for 6a. The bonding parameters involving Au are similar to those reported for (2-Cl 2 AuC 6 H 4 )Ph 2 P]NePh, as are the CeN and N]P bond lengths [6].…”
Section: Crystal Structures Of the Gold(iii) Complexes 6a And 6csupporting
confidence: 78%
“…Monitoring of the reaction by 31 P NMR and ESI-MS showed that the intermediate mercurated iminophosphorane, 5a, had fully formed after 1.5 h. Removal of the solvent gave 5a which was used directly, after characterisation by 31 P NMR and ESI-MS. The ion [AuCl 4 ] À has been used to produce gold(III) iminophosphoranes [6,17,30]. To 5a was added [NMe 4 ][AuCl 4 ] and dry acetonitrile and the mixture stirred for several days in the dark.…”
Section: Complexes Of Glycosyl Iminophosphoranesmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have reported on the biological [1518] and catalytic [1921] applications of iminophosphorane or iminophosphine derivatives of gold(III) (selected examples in Fig. 1) [15,16].…”
Section: Introductionmentioning
confidence: 99%